Impact Of Corporate Taxation On Dividend Policy Of Quoted Firms In Nigeria - OLOYEDE, John Adebayo; OLAOYE, Clement Olatunji; OLUWALEYE, Taiwo Olarinre (Advances in Social Sciences Research Journal, 2018)
This study examined the impact of corporate taxation on dividend policy of selected quoted firms in Nigeria. Specifically, it analyzed the impact of company income tax and educational tax on dividend per share of 10 randomly sampled consumer goods firms. Data used were collected from the published annual reports of the selected firms over a period of 5 years spanning from 2011 to 2015. Panel data estimation techniques employed in the study are pooled OLS estimation, fixed effect estimation and random effect estimation. The most consistent and efficient estimation result showed that company income tax has insignificant positive impact on dividend per share β=.0000659 (p=0.705 > 0.05), education tax exert insignificant positive impact on dividend per share β=0.0142983 (p=0.088 > 0.05). It was concluded in the study that corporate taxation has no clear cut influence on dividend distribution policy of quoted consumer goods firms in Nigeria. Thus, firms are advised to devise investment and financing framework that will give room for adequate and consistent dividend distribution, and strive toward capacity expansion and operational efficiency to foster increased profitability, which is a sine-qua-non for higher dividend distribution.